THE ROLE OF FINANCIAL LITERACY AND FINANCIAL ATTITUDE IN INCREASING INCOME - Hikmah, Nurul; Munawarah, Munawarah; Darman, Darman; Risendy, Rian (Universitas Nusa Cendana, 2025)
This research investigates the impact of financial literacy and financial attitudes on MSME income in South Palu using a quantitative approach. Primary data was collected directly from respondents through questionnaires, with data sources coming from MSME owners in the South Palu region. SPSS was used for data analysis. The findings reveal that both financial literacy and financial attitudes significantly contribute to increasing MSME income. MSME owners with strong financial literacy can allocate budgets efficiently, cut unnecessary expenses, and optimize business potential. Positive financial attitudes, such as discipline, financial commitment, and prioritizing decision-making, form the core of business success. Financial attitudes play a more substantial role than financial literacy, as they are more directly applicable in decision-making. Financial literacy offers the knowledge, but without the right attitude, it remains theoretical and ineffective in practice. Keywords: Financial Literacy; Financial Attitude; MSME Income; MSME